Antifungal activity of two oxadiazole compounds for the paracoccidioidomycosis treatment - Rodrigues-Vendramini, Franciele Abigail Vilugron (PLoS Negl Trop Dis, 2019)
Paracoccidioidomycosis (PCM) is a neglected disease present in Latin America with difficulty in treatment and occurrence of serious sequelae. Thus, the development of alternative therapies is imperative. In the current work, two oxadiazole compounds (LMM5 and LMM11) presented fungicidal activity against Paracoccidioides spp. The minimum inhibitory and fungicidal concentration values ranged from 1 to 32 μg/mL, and a synergic effect was observed for both compounds when combined with Amphotericin B. LMM5 and LMM11 were able to reduce CFU counts (≥2 log(10)) on the 5(th) and 7(th) days of time-kill curve, respectively. The fungicide effect was confirmed by fluorescence microscopy (FUN-1/FUN-2). The hippocratic screening and biochemical analysis were performed in Balb/c male mice that received a high dose of each compound, and the compounds showed no in vivo toxicity. The treatment of experimental PCM with the new oxadiazoles led to significant reduction in CFU (≥1 log(10)). Histopathological analysis of the groups treated exhibited control of inflammation, as well as preserved lung areas. These findings suggest that LMM5 and LMM11 are promising hits structures, opening the door for implementing new PCM therapies.